LEVELS AND CLASSIFICATION OF HADITH CRITICS: A LITERATURE STUDY - Halimah, Ulfatul (Nabawi: Journal of Hadith Studies, 2024)
Observing the dark historical events concerning hadis experienced by Muslims, it is deemed important to separate the authenticity of the sanad and matan. Therefore, hadis scholars have conducted comprehensive critical studies on both the matan and sanad of hadis, without neglecting the close relationship between the two. In hadis science, criticism of the sanad becomes a benchmark for the validity of hadis authenticity, where the authenticity of a sanad free from jarh (criticism) is the main indicator. This article further discusses the groups of hadis narrator critics. This research is categorized as library research, focusing on the analysis and interpretation of written materials based on their context. The data collection technique used is documentation, by gathering various literary works, theses, dissertations, articles, and other scientific information closely related to the discussed theme. This research concludes that there are several categories of hadis narrator critics with different views in determining the authenticity of hadis narrators. These categories influence legal rulings since each group of hadis critics has its own criteria for determining hadis authenticity.[Mengamati peristiwa sejarah kelam hadis yang pernah dilalui umat Islam, dirasa penting untuk memisahkan antara kesahihan sanad dan matan. Oleh karena itu, ulama hadis melakukan kajian kritik yang komprehensif dari sisi matan hadis dan sanad, dengan tidak meniadakan hubungan erat di antara keduanya. Dalam ilmu hadis, kritik sanad menjadi tolok ukur validitas kesahihan hadis, di mana kesahihan sanad yang jauh dari jarh (celaan) menjadi indikator utama. Artikel ini membahas lebih lanjut mengenai golongan kritikus periwayat hadis. Penelitian ini tergolong penelitian pustaka (library research) yang memfokuskan diri pada analisis dan interpretasi bahan tertulis berdasarkan konteksnya. Teknik pengumpulan data yang digunakan adalah dokumentasi, yaitu dengan mengumpulkan berbagai karya pustaka, tesis, disertasi, artikel, dan bentuk informasi ilmiah lainnya yang berkaitan erat dengan tema yang dibahas. Penelitian ini menyimpulkan bahwa terdapat beberapa kategori kritikus periwayat hadis yang memiliki pandangan berbeda dalam menentukan kesahihan periwayat hadis. Adanya kategori ini akan menentukan hukum, karena setiap golongan kritikus hadis mempunyai syarat masing-masing dalam menentukan kesahihan hadis.]